A Guidebook on B2C Cross-border E-commerce Operation to China for Thai SME Products - Fan Caiyun (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
With the development of information technology and mobile phone use, cross-border e-commerce (CBEC) now has been a popular trend of the global economy. However, even cross-border e-commerce business is fast growing in worldwide, in Thailand is still in its infancy, and Thai Northern SMEs are limited to get knowledge for doing cross-border e-commerce to China. Regarding this, to help Thai SMEs to increase their product’s exporting to the Chinese market, this research aims to design a cross-border e-commerce business operating guidebook by using supply chain management theory, and tools integrating Kano model, Common KADS, and learning in action. This research process is divided into four stages according to Knowledge management stages, which are knowledge identification, knowledge acquisition, and then organizing and representation, finally evaluation. In detail, supply chain management with information flow, financial flow and logistic flow is the theoretical basis and mainframe of this article. This research aims to identify the SMEs’ requirement of different factors during the cross-border e-commerce business process. Then, based on results of Kano questionnaire, knowledge capturing is conduct by i) common KADS interview to domain experts, an owner of Taobao platform and Alipay, and manager of Y logistic company Chiang Mai International Set Center are identified as domain knowledge experts; ii) learning in action, means that actually operating by the guideline of expert’s knowledge, which help in deeper understanding and detailed knowledge capturing. Knowledge map helps in organizing and presenting strategic knowledge in three layers: task knowledge layer, inference knowledge layer and domain knowledge layer. The final results of the guidebook consist of three parts, which are information flow, financial flow a logistic flow. Following with the knowledge captured from both domain expert by common KADS interviewing and learning in action, it can be concluded and presented by knowledge map that: a) there is three task knowledge in the process of Taobao information channel, product online releasing, online selling and delivery; b) customer refund is the knowledge in task layer during Alipay financial process; c) shipping information setting, custom recording of products, and logistic order are the task knowledge in logistic flow from Thailand to China, those are the contents for guidebook designing.